2011
DOI: 10.1175/2009jcli3170.1
|View full text |Cite
|
Sign up to set email alerts
|

Seasonally Modulated Tropical Drought Induced by Volcanic Aerosol

Abstract: Major volcanic events with a high loading of stratospheric aerosol have long been known to cause cooling, but their impact on precipitation has only recently been emphasized, especially as an analog for potential geoengineering of climate. Here, the authors use a coupled atmosphere-ocean-land-vegetation model in conjunction with observations to study the effects of volcanic aerosol on the tropical and subtropical precipitation. The small internal variability in the model enables a clear identification of the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
93
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(118 citation statements)
references
References 47 publications
25
93
0
Order By: Relevance
“…8, 9 and 11) is in agreement with several papers that identified a precipitation surplus over Australia following large volcanic eruptions (Schneider et al, 2009;Joseph and Zeng, 2011). Our results suggest that the direct effect of volcanic aerosols on precipitation overrode the impact of the IOD and ENSO on Australian precipitation in the years following large tropical volcanic eruptions.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…8, 9 and 11) is in agreement with several papers that identified a precipitation surplus over Australia following large volcanic eruptions (Schneider et al, 2009;Joseph and Zeng, 2011). Our results suggest that the direct effect of volcanic aerosols on precipitation overrode the impact of the IOD and ENSO on Australian precipitation in the years following large tropical volcanic eruptions.…”
Section: Discussionsupporting
confidence: 91%
“…The direct radiative effect of volcanic aerosols has been found to cause global precipitation deficits for up to 5 years post-eruption (Robock and Lui, 1994;Iles et al, 2013Iles et al, , 2015Gillett et al, 2004;Gu and Adler, 2011;Soden et al, 2002;Joseph and Zeng, 2011;Schneider et al, 2009;Timmreck et al, 2012). However, these deficits have been shown to vary seasonally (Joseph and Zeng, 2011), and cause positive precipitation anomalies over the north-west (NW) and southeast (SE) of Australia in the Southern Hemisphere (SH) winter and early spring (July to September), despite significant precipitation deficits in the summer (Joseph and Zeng, 2011;Schneider et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2). This is in agreement with previous studies (Iles et al, 2013;Joseph and Zeng, 2011). In the global precipitation-maps, we see a reduction of precipitation for both experiments through the volcanic aerosol in most regions in the first four prediction years (Fig.…”
Section: Precipitationsupporting
confidence: 93%
“…Joseph and Zeng [87] employed a coupled atmosphere-ocean-land-vegetation model of intermediate complexity to study the volcanic aerosol effect on tropical precipitation. They found that the precipitation response over the ocean is slower and weaker than over the land due to the ocean's larger thermal capacity.…”
Section: P0135mentioning
confidence: 99%